Menelisik Persepsi Harga, Store Atmosphere dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Sendiri Coffee Bar - Ni Putu Desy Darmayanti; I Wayan Sunia; Ni Putu Nina Eka Lestari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Understanding consumer behavior is very important because it can be used as important capital for companies to achieve consumer satisfaction. This research was conducted at Sendiri Coffee Bar located at Jl. Tukad Pakerisan No. 69, Denpasar, Bali. Based on transaction data, a total of 7,072 customers were obtained. Determination of the number of samples in this study by Hair et al. (2017), namely a minimum of 5–10 respondents for each indicator in the questionnaire. So the number of samples is 168 respondents. The types of data are Quantitative data and Qualitative data sourced from Primary Data and Secondary Data. Data collection techniques through Documentation, Questionnaires and Online Data Searching / Internet Searching. As for the Data Analysis Techniques from Instrument Testing, Statistical Analysis with stages of data analysis, namely: Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Multiple Linear Regression Analysis, R2 Determination Coefficient, Partial Regression Significance Test (t Test) and Simultaneous Regression Significance Test (F Test). The results of the study that partially have a positive and significant influence between the price perception variable (X1) on customer satisfaction (Y), obtained a t-count value of 9.017 with a significance level value of 0.000, Partially have a positive and significant influence between the Store Atmosphere variable (X2) on customer satisfaction (Y), obtained a t-count of 14.169 with a significance level value of 0.000, Partially have a positive and significant influence between the Service Quality variable (X3) on customer satisfaction (Y), obtained a t-count of 9.567 with a significance level of 0.188, and simultaneously there is a positive and significant influence between the influence of price perception (X1), Store Atmosphere (X2) and Service Quality (X3) on customer satisfaction (Y), obtained F count of 150.722 with a significance value of 0.000.